2014
DOI: 10.1257/aer.104.4.1350
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of Conflict: An Economic Model

Abstract: Mutual benefits from trust and cooperation not withstanding, inter-group conflict is pervasive. In his study of the Peloponnesian War, Thucydides (2000) traces the origins of conflict as much to fear and distrust as to other factors such as greed and honor. He argues that the Peloponnesian War became inevitable precisely because each side saw war as inevitable and did not want to relinquish the first mover advantage to the other (see also Kagan 2004).1 This view of conflict, sometimes referred as the Hobbesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…This makes the option for war as a means of appropriating power to look more appealing even if the cost of engagement is multiplied. In Cunningham (2013), indirect negotiations may fail because outside mediators may have ulterior motives beyond just ending the fighting, while Acemoglou and Wolitzky (2014) argue that incomplete information about rival's intentions may lead one side to interpret noisy signals as opportunistic tactics by the other. Thus it may opt to respond in a similar manner and, finally, each side maximizes its own aggression leading to 'conflict spirals'.…”
mentioning
confidence: 99%
“…This makes the option for war as a means of appropriating power to look more appealing even if the cost of engagement is multiplied. In Cunningham (2013), indirect negotiations may fail because outside mediators may have ulterior motives beyond just ending the fighting, while Acemoglou and Wolitzky (2014) argue that incomplete information about rival's intentions may lead one side to interpret noisy signals as opportunistic tactics by the other. Thus it may opt to respond in a similar manner and, finally, each side maximizes its own aggression leading to 'conflict spirals'.…”
mentioning
confidence: 99%
“…Much recent work employing dynamic contest models attempts to account for the empirical observation that there are many persistent intergroup conflicts (e.g., Baliga et al, 2011;Rohner et al, 2013;Acemoglu and Wolitzky, 2014;Gul and Pesendorfer, 2012), and this growing theoretical literature has been complemented by observational studies testing competing explanations of conflict persistence (e.g., Augenblick, 2016;Takahashi, 2015).…”
Section: Dynamic Models Of Conflictmentioning
confidence: 99%
“…While ethnicity is a key contextual factor, this study focuses on the persistence of conflict or the formation of "conflict spirals", and it is shown that coercive peace policies such as external peacekeeping cannot diminish such spirals in the long term. In a more general but analogous setting of competing teams, Acemoglu and Wolitzky (2014) They show that one party becomes more aggressive if its cost decreases or its opponent's cost increases, and that the decision maker is better off when the two parties are closely matched.…”
Section: Dynamic Models Of Conflictmentioning
confidence: 99%
“…() is more similar to my article in that they model distorted stereotypes of other social groups as based on biased belief formation; however, their model is quite different overall as it does not study dislike. Acemoglu and Wolitzky () show how cycles of conflict between groups can arise due to misperceptions (“good” actions are misperceived as “bad”), causing beliefs about the quality of the other side's character to decline. In their model, actions are binary and a spiral of conflict is a sequence of periods in which both parties play bad actions (as opposed to actions actually becoming more extreme over time).…”
Section: Additional Related Literaturementioning
confidence: 99%